Simulation of β-induced Alfvén eigenmode instabilities and mode transition for HL-3 hybrid scenario - Yunpeng Zou; Vincent S Chan; Yasushi Todo; Ruirui Ma; Miao Xue; Xiaoran Zhang; Yiren Zhu; Wei Chen (Nuclear Fusion)
A kinetic-magnetohydrodynamic hybrid simulation is performed to investigate the Alfvén eigenmode (AE) and fishbone (FB)/FB-like (FBL) instabilities excited by neutral beam injection (NBI)-deposited energetic particles (EPs) in an HL-3 hybrid scenario. The hybrid scenario is characterized by a flat q -profile in the core due to off-axis electron cyclotron current drive (ECCD). A nonlinear simulation with multiple toroidal mode numbers indicates that the n = 2 β -induced AE (BAE) is excited initially in the linear stage and the n = 1 FB mode has the highest nonlinear saturation level. The EP distribution is modified only slightly in both real and velocity space from its initial state because of a narrow mode structure near the axis. Focusing on the n = 2 mode, sensitivity analysis indicates that mode activity and transition depend on the EP pressure, injected energy, and q -profile. The dominant unstable mode deviates from FBL mode to BAE by raising the EP pressure, and from BAE to toroidicity-induced AE by raising the. NBI injected energy. The mechanism is interpreted through a resonant condition and a corresponding transition threshold is observed. In addition, extending the flat shear region could increase the BAE width, resulting in stronger EP transport. Furthermore, a nonlinear simulation only considering n = 1 and n = 2 modes demonstrates that the low-energy EPs, as intermediates, gain energy from n = 2 mode, which subsequently transfers energy to the n = 1 mode through resonant interaction.